2018
DOI: 10.18203/2320-6012.ijrms20183637
|View full text |Cite
|
Sign up to set email alerts
|

A study of knowledge, attitude and practice in diabetic retinopathy among patients attending a primary health care centre

Abstract: Background: Diabetic retinopathy is a major cause of preventable blindness. Sufficient knowledge about the disease can prevent sight threatening complications. Aim of this study is to evaluate the knowledge and its influence on attitude and practice in diabetic retinopathy among patients attending a primary health centre.Methods: A knowledge attitude practice questionnaire was prepared and pretested in a sample group of representative population. The response was analyzed as to whether the questions were under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
3
1
1
Order By: Relevance
“…proportion of good knowledge of diabetic retinopathy in this study was found to be 41.3% (95% CI (36.8-46.1)). This result was in line with studies done in South Africa (42%) [19], India Kerala (39.19%) [20], and India Chennai (37.1%) [21].…”
Section: Discussionsupporting
confidence: 92%
“…proportion of good knowledge of diabetic retinopathy in this study was found to be 41.3% (95% CI (36.8-46.1)). This result was in line with studies done in South Africa (42%) [19], India Kerala (39.19%) [20], and India Chennai (37.1%) [21].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study reveal the overall assessment of patients' knowledge regarding diabetic's retinopathy; the finding indicates that patients among the study sample show poor level of knowledge (55.0%). These results are consistent with (16) who reported that half of the respondents (60.8%) had no knowledge of diabetic retinopathy.…”
Section: Overall Assessment Of Patient Knowledge Regarding Diabetic's Retinopathysupporting
confidence: 92%
“…The results of the current study showed that, there was a statistically significant relation between DR patients' educational level and their total knowledge as it was evident that, the total knowledge score was higher among those with higher educational level. This was congruent with a study of Geethadevi et al (2018) who found that, good knowledge was positively associated with higher educational level. In addition, Seneviratne and Prathapan (2016) reported the same result.…”
Section: Self-care Practices Of the Studied Groups During Different P...supporting
confidence: 89%
“…Also, Memon et al (2015) found the same result. However, this result was incongruent with that of Geethadevi et al (2018) who found that, females were more knowledgeable about DR than males. Our result might be because most of females in our study were housewives and they had lower interactions compared with males who were working and thus they were prone to gain more knowledge about DR from different sources.…”
Section: Self-care Practices Of the Studied Groups During Different P...contrasting
confidence: 83%